Environmental Sustainability in Transport Policy: How is the Situation in Denmark, The Netherlands and Sweden? - Tengström, Emin (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
Environmental sustainability has been an important political issue since the publication in 1987 of the report of the World Commission on Environment and Development entitled Our Common Future and its introduction of the concept of 'sustainable development’. The concept of en-vironmental sustainability has, for instance, often been used in documents on transport policy in many countries. The aim of this lecture is to analyse the situation in Denmark, the Netherlands and Sweden and to assess the results of the national transport policies as far as environmental sustainability is concerned. My lecture is based upon a recent study entitled Towards Environmental Sustainability? A Comparative Study of Danish, Dutch and Swedish Transport Policies in a European Context. It will be published by a British publisher (Ashgate) within one or two months. My lecture is organised in the following way: I will begin with a discussion of the reaction of national politicians to the complex environmental problems of transport. Thereafter, I will introduce and define the concept of <ecological modernisation capacity’ and identify some conflicts between efficiency, safety, equity and environmental sustainability in transport. After that, I will evaluate the results of present policies aiming at the attainment of some intermedi- ate objectives related to environmental sustainability and, finally, try to explain the outcome of national transport policies in Denmark, the Netherlands and Sweden as far as environmen- tal sustainability is concerned.